Development of Inquiry Based Modules in Biology Subjects - Gustina, Melli; Mustika Sarjani, Tri; Fitria, Dini (Bioilmi: Jurnal Pendidikan, 2024)
At this time teachers are expected to be able to design teaching materials that can help students achieve learning objectives and teaching materials that can be an independent learning resource that provides a series of lessons presented in a structured format. Modules are teaching materials that can be used to achieve learning objectives. The purpose of this study is to assess the feasibility and usefulness of products that have been developed, especially inquiry-based modules for the subject of Biology MAN 1 Langkat. This research refers to research and development (R&D) methods. The development model used in this study is the Borg and Gall model which is modified into 6 stages. Based on data analysis, the results of material expert validation in all aspects were obtained with a percentage of 93.93% with very feasible criteria, up from 91.51%. After improvements, the results of the validation of media experts reached 80% with feasible criteria, up from 70%. The results of linguist validation in all aspects with a percentage of 80%, after improvements were made increased to 87.69% with very feasible criteria. The average student response was 89.58% with convenient criteria, while the average teacher response was 100% with very practical criteria in both samples. Therefore, modules with material on the diversity of living things that have been made can be applied in schools in class X.